Identifying features of apps to support using evidence-based language intervention with children. Issue 6 (1st November 2020) - Heyman, Nikki
ABSTRACT: This study investigated the features of apps that speech–language pathologists (SLPs) deem to be beneficial for language intervention with children. The study employed an explanatory, sequential mixed-method approach. A self-developed online survey was distributed to SLPs ( n = 338) who use apps. This was followed by a semi-structured interview with some participants ( n = 16) in order to obtain further insights from the survey. The findings indicated that SLPs view apps as an engaging and motivating tool for therapy to facilitate their intervention goals. Specific content and design features of apps may support effective language intervention. However, these features need to be carefully evaluated in terms of the underlying principles of language intervention, multimedia learning, and learning. In addition, features of apps that may impede effective intervention must also be considered. The findings from the study highlight the need for SLPs to engage more deeply with the theory underlying multimedia learning and identify the active ingredients used in treatment. This information can be used to contribute to evidence-based practice when using apps for intervention. A feature-matching checklist was developed in order to guide SLPs in selecting apps based on the features of the app to facilitate language intervention.